2022
DOI: 10.3389/fcvm.2022.735906
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Electronic Frailty Index for Predicting Mortality and Complications Analysis in Pulmonary Hypertension Using Random Survival Forest Model

Abstract: BackgroundThe long-term prognosis of the cardio-metabolic and renal complications, in addition to mortality in patients with newly diagnosed pulmonary hypertension, are unclear. This study aims to develop a scalable predictive model in the form of an electronic frailty index (eFI) to predict different adverse outcomes.MethodsThis was a population-based cohort study of patients diagnosed with pulmonary hypertension between January 1st, 2000 and December 31st, 2017, in Hong Kong public hospitals. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…In a similar study done by Zhou J et al ., it has been identified that, significant number of patients with PH were frail with higher risk of mortality and this can be used as a basis for clinical evaluation and shall be considered in PH treatment plans. [ 5 9 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study done by Zhou J et al ., it has been identified that, significant number of patients with PH were frail with higher risk of mortality and this can be used as a basis for clinical evaluation and shall be considered in PH treatment plans. [ 5 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Identifying frailty and pre frailty in patients with CRDs is emerging as an important vital sign. [ 9 ] Frailty is progressive, but some of the driving factors are modifiable, and it can be reversed, especially when intervened at pre-frail stages.…”
Section: Introductionmentioning
confidence: 99%
“…This system hosts data on disease diagnosis, laboratory results, past comorbidities, clinical characteristics and medication prescriptions. The system has been used by our Hong Kong research team to perform comparative studies [11,12,13]. This study was approved by the Institutional Review Board of the University of Hong Kong/Hospital Authority Hong Kong West Cluster and The Joint Chinese University of Hong Kong-New Territories East Cluster, and complied with the Declaration of Helsinki.…”
Section: Study Populationmentioning
confidence: 99%